Nitrogênio e potássio na adubação de capim piatã em solo do cerrado matogrossense - Morais, Léa Paula Vanessa Xavier Corrêa de (2015)
In Brazil, the area with cultivated pastures occupies more than 100 million hectares, of which 70% is occupied by forage grasses genus Brachiaria. The absence of nitrogen and potassium fertilizers is one of the main limiting factors for animal production on pasture in the Cerrado. Nitrogen and potassium deficiencies can affect chlorophyll synthesis, crude protein content in plant tissues and various metabolic functions. The objective was to evaluate the interaction of nitrogen and potassium dosages on fertilization and its effects on the nutritional and productive characteristics of Brachiaria brizantha cv. BRS Piatã grown in Oxisol of the Cerrado. It was used five doses of nitrogen (0, 100, 200, 300 and 400 mg dm-3 ) and five doses of potassium (0, 90, 180, 270 and 360 mg dm-3 ), in a factorial scheme 5x5. The experimental design was completely randomized with four replications. Three cuts were made in the shoot of the plants at intervals of 30 days. The first two cuts were at 5 cm from the lap of the plants and the third and final cut close to the lap of the plants. The variables analyzed were: plant height, SPAD reading, number of leaves and tillers, dry weight of shoot, leaves, stems and roots and nitrogen concentration in leaves. The results were submitted to variance analysis for the combinations of nitrogen and potassium doses and study of regression at 5% of probability using the statistical program Statistical Analysis System. The nitrogen and potassium doses significantly increase the productive characteristics of piatã grass. Increasing doses of nitrogen doses decreases the concentration of potassium in the diagnostic leaves of piatã grass. Generally, the nitrogen-potassium relation was approximately 1:1 for the best results of the evaluated characteristics.